Prevalence of diabetes among children treated with growth hormone in Israel. Issue 10 (21st February 2019) - Lutski, M.; Zucker, I.; Zadik, Z.; Libruder, C.; Blumenfeld, O.; Shohat, T.; Laron, Z.
Abstract: Aims: To determine the long‐term risk of diabetes in a cohort of children treated with recombinant human growth hormone in Israel, using data from the Israeli National Diabetes Register. Methods: Between 1988 and 2009, 2513 children were approved for growth hormone treatment. They were assigned to one of two groups. The first group included children treated for isolated growth hormone deficiency and who were small for gestational age and the second included those treated for multiple pituitary hormone deficiency, chronic renal failure, Turner syndrome or Prader–Willi syndrome. The cohort was cross‐linked with the Israeli National Diabetes Register for 2014 (mean follow‐up duration 12.1±5.3 years), and prevalent cases of diabetes were identified. Standardized prevalence ratios for diabetes were calculated for people aged 10–29 years. Results: In 2014, a total of 23 individuals were identified with diabetes (four with pre‐existing diabetes, seven developed diabetes before age 17 years and 12 developed it at a later age). In the isolated growth hormone deficiency and small‐for‐gestational‐age group there was no difference in the prevalence of diabetes compared with the general population (standardized prevalence ratio 2.05, 95% CI 0.94–3.89). In the group that included people with multiple pituitary hormone deficiency, chronic renal failure, Turner syndrome and Prader–Willi syndrome there was a significantly higher diabetes prevalence (standardized prevalence ratio 11.94, 95% CI 6.53–20.00) compared with the general population. Conclusions: No difference in diabetes prevalence was found in the isolated growth hormone deficiency and small‐for‐gestational‐age group, compared with the general population. Children treated with growth hormone with pre‐existing risk factors had an increased prevalence of diabetes. It is advisable to monitor blood glucose levels closely during and after growth hormone treatment, especially in such children. What's new?: This study reinforces the findings of previous studies indicating that growth hormone (GH) treatment is not associated with greater diabetes prevalence in individuals with isolated GH deficiency. In individuals with pre‐existing risk factors for diabetes there is an increased prevalence of diabetes both during GH treatment and after treatment cessation. In high‐risk individuals, glucose should be closely monitored both during and after cessation of GH treatment.